A New Multilevel Inverter Topology for Grid-Connected Photovoltaic Systems - Muhammad Bilal Satti; Ammar Hasan; Mian Ilyas Ahmad (International Journal of Photoenergy)
The demand for clean and sustainable energy has spurred research in all forms of renewable energy sources, including solar energy from photovoltaic systems. Grid-connected photovoltaic systems (GCPS) provide an effective solution to integrate solar energy into the existing grid. A key component of the GCPS is the inverter. The inverter can have a significant impact on the overall performance of the GCPS, including maximum power point (MPP) tracking, total harmonic distortion (THD), and efficiency. Multilevel inverters are one of the most promising classes of converters that offer a low THD. In this paper, we propose a new multilevel inverter topology with the motivation to improve all the three aforementioned aspects of performance. The proposed topology is controlled through direct model predictive control (DMPC), which is state of the art in control techniques. We compare the performance of the proposed topology with the topologies reported in literature. The proposed topology offers one of the best efficiency, MPP tracking, and voltage THD.